Iris authentication through Gabor filter using DSP processor - Saravanan, V.; Sindhuja, R. (2013 IEEE Conference on Information and Communication Technologies, 2013)
BIOMETRICs is the measurement of one's physiological or behavioural characteristics for security purposes. There are many types of biometrics available including finger print, voice scanner, retinal, iris recognition. Among this biometric authentication Iris recognition offers great amount of security and it has more advantages over other types of Biometric authentication methods. This paper analyses the iris biometric authentication as it have low error rates compared to other biometric authentication methods and its robustness of the algorithms provided. Various types of feature extraction are already available like Haar wavelet transform,1-d dyadic wavelet transform but they are limited to their application. This paper uses Gabor filters for feature extraction methods for iris authentication, which is more advantageous than already available methods. Matching algorithms such as binary Hamming distance and Euclidean distance is used in this paper for comparing the Feature extraction methods. After the Features are extracted it is implemented in Analog devices to achieve fast verification Performance.